Tourist socio-cultural aversions: A holistic conceptual framework. (December 2021) - Holder, Afiya; Ruhanen, Lisa; Mkono, Mucha; Walters, Gabrielle
Abstract: Socio-cultural sensitivities such as xenophobia, racism, and other forms of prejudice impact demand for tourism products and experiences. Existing studies on these phenomena have tended to be framed through singular or binary lenses, and a holistic exploration and conceptualisation to inform tourist behaviour research is absent. This paper fills this critical gap by conceptualising tourist socio-cultural aversions that underpin tourists' avoidance of destinations, products and experiences. Two theoretical contributions are made: (1) a tourist socio-cultural aversion typology is proposed; and (2) the complexities of implicit and explicit, as well as aggressive and passive aversions, are explored. The paper highlights key managerial implications of aversions and in doing so, provides businesses, the tourism sector, and government agencies with an understanding of tourists implicit or explicit aversions to particular destinations or products. The socio-cultural and economic ramifications for individuals, businesses and communities is considerable if left unaddressed. Highlights: Explores the nature and impacts of socio-cultural aversions in tourism. Conceptualises a tourist socio-cultural aversion typology. Socio-cultural aversions of a passive-implicit nature can have a transformative impact. Socio-cultural aversions intersect multiple quadrants and are challenging to identify and address.